Toward Strong Near‐Infrared Absorption/Emission from Carbon Dots in Aqueous Media through Solvothermal Fusion of Large Conjugated Perylene Derivatives with Post‐Surface Engineering. Issue 23 (2nd June 2022) - Liu, Yupeng; Lei, Josh Haipeng; Wang, Gang; Zhang, Zhiming; Wu, Jun; Zhang, Bohan; Zhang, Huiqi; Liu, Enshan; Wang, Liming; Liu, Tzu‐Ming; Xing, Guichuan; Ouyang, Defang; et al.
Abstract: Carbon dots (CDs) have attracted significant interest as one of the most emerging photoluminescence (PL) nanomaterials. However, the realization of CDs with dominant near‐infrared (NIR) absorption/emission peaks in aqueous solution remains a great challenge. Herein, CDs with both main NIR absorption bands at 720 nm and NIR emission bands at 745 nm in an aqueous solution are fabricated for the first time by fusing large conjugated perylene derivatives under solvothermal treatment. With post‐surface engineering, the polyethyleneimine modified CDs (PEI‐CDs) exhibit enhanced PL quantum yields (PLQY) up to 8.3% and 18.8% in bovine serum albumin aqueous and DMF solutions, which is the highest PLQY of CDs in NIR region under NIR excitation. Density functional theory calculations support the strategy of fusing large conjugated perylene derivatives to achieve NIR emissions from CDs. Compared to the commercial NIR dye Indocyanine green, PEI‐CDs exhibit excellent photostability and much lower cost. Furthermore, the obtained PEI‐CDs illustrate the advantages of remarkable two‐photon NIR angiography and in vivo NIR fluorescence bioimaging. This work demonstrates a promising strategy of fusing large conjugated molecules for preparing CDs with strong NIR absorption/emission to promote their bioimaging applications. Abstract : Carbon dots with both main near‐infrared (NIR) absorption and emission bands in aqueous solution are fabricated through solvothermal fusion of large conjugated perylene derivatives. After post‐surface modification with polyethyleneimine, high photoluminescence quantum yields in NIR region up to 8.3% and 18.8% are obtained in their bovine serum albumin aqueous and DMF solutions, respectively.